1D modelling and preliminary analysis of the coupled DYNASTY–eDYNASTY natural circulation loop - Benzoni, Gabriele; Introini, Carolina; Lorenzi, Stefano; Loi, Lorenzo; Cammi, Antonio (Frontiers in Energy Research, 2023)
In the continuous strive to improve the safety of current-generation and next-generation nuclear power plants, natural circulation can be used to design passive safety systems to remove the decay heat during the shutdown. The Molten Salt Fast Reactor (MSFR) is a peculiar type of Gen-IV nuclear facility, where the fluid fuel is homogeneously mixed with the coolant. This design leads to natural circulation in the presence of an internally distributed heat source during the shutdown. Furthermore, to shield the environment from the highly radioactive fuel, an intermediate loop between the primary and the secondary loops, able to operate in natural circulation, is required. To analyze the natural circulation with a distributed heat source and to study the natural circulation of coupled systems and the influence of the intermediate loop on the behaviour of the primary, Politecnico di Milano designed and built the DYNASTY-eDYNASTY facility. The two facilities are coupled with a double-pipe heat exchanger, which siphons heat from DYNASTY and delivers it to the eDYNASTY loop. This work focuses on modelling the coupled DYNASTY-eDYNASTY natural circulation loops using DYMOLA2023®, an integrated development environment based on the Modelica Object-Oriented a-causal simulation language. The 1D Modelica approach allows for building highly reusable and flexible models easing the design effort on a complex system such as the DYNASTY-eDYNASTY case without the need to rewrite the whole model from scratch. The coupled models were developed starting from the already-validated single DYNASTY model and the double-pipe heat exchanger coupling. The models were tested during the whole development process, studying the influence of the numerical integration algorithm on the simulation behaviour. A preliminary analysis of both the adiabatic and the heat loss models analyzed the effect of the secondary natural circulation loop on the behaviour of the DYNASTY loop. The simulation results showed that the eDYNASTY loop dampens the behaviour of the primary DYNASTY loop. Furthermore, a parametric analysis of the DYNASTY and the eDYNASTY coolers highlighted the influence of the cooling configuration on the facility’s behaviour. Finally, the simulation results identified the most critical aspects of the models in preparation for an experimental comparison.